2013
DOI: 10.1371/journal.pntd.0002035
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis, Treatment and Risk Factors of Strongyloides stercoralis in Schoolchildren in Cambodia

Abstract: BackgroundWorldwide, an estimated 30 to 100 million people are infected with Strongyloides stercoralis, a soil-transmitted helminth. Information on the parasite is scarce in most settings. In semi-rural Cambodia, we determined infection rates and risk factors; compared two diagnostic methods (Koga agar plate [KAP] culture and Baermann technique) for detecting S. stercoralis infections, using a multiple stool examination approach; and assessed efficacy of ivermectin treatment.Methods/Principal FindingsWe perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
96
3
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(115 citation statements)
references
References 42 publications
(51 reference statements)
14
96
3
2
Order By: Relevance
“…Almost all these studies have focused on Ascaris lumbricoides (2-40%), Hook worm (3.4-65%), Trichuris trichiura (0.4-17.3%), and Strongyloides stercoralis (0.4-31.5%) in communities and hospitals. [6][7][8][9][10][11][12][13] The Cambodian Ministry of Health has implemented national deworming programs. However, mass treatment has only focused on the most common parasites, such as A. lumbricoides, Hook worm, and T. trichiura.…”
Section: Introductionmentioning
confidence: 99%
“…Almost all these studies have focused on Ascaris lumbricoides (2-40%), Hook worm (3.4-65%), Trichuris trichiura (0.4-17.3%), and Strongyloides stercoralis (0.4-31.5%) in communities and hospitals. [6][7][8][9][10][11][12][13] The Cambodian Ministry of Health has implemented national deworming programs. However, mass treatment has only focused on the most common parasites, such as A. lumbricoides, Hook worm, and T. trichiura.…”
Section: Introductionmentioning
confidence: 99%
“…In 2009, LTE were observed in the stools of 27/150 schoolchildren (18.0%) in the Damrei Chhlang village primary school, Kandal province, Cambodia, during a standard parasitological survey using the Kato-Katz technique (Khieu et al, 2013). Given the high prevalence of Fasciola spp.…”
Section: Introductionmentioning
confidence: 99%
“…Results are available within two days, although extended incubation up to four days increases yield 8,11,12 .…”
Section: Stool Microscopy and Culture Methodsmentioning
confidence: 99%
“…Two studies comparing 48 h APC with Baermann culture found an improved recovery of S. stercoralis larvae in APC 11,12 . Recovery rates improve markedly with multiple stool cultures 6,11,13 …”
Section: Stool Microscopy and Culture Methodsmentioning
confidence: 99%